Inflation, monetary pain, fiscal relief - Kutasi, Gábor; Czeczeli, Vivien; Szalai, Piroska (Public Finance Quarterly, 2024)
Katalin Botos, in issue 2023/4 of Pulic Finance Quarterly, examined the causes of inflation in the crisis years of 2020, its management, which she considers inadequate, and finally its fiscal impact. On the occasion of her assessment of the inflationary period, we reflect on her thoughts on impoverishment and fiscal sustainability with extended time series as the inflationary rollercoaster has passed. Our analysis is based on the Modern Monetary Theory (MMT), which was launched its scientific career in the USA. MMT paradigm is that dealing with high inflation through monetary tightening inevitably leads to recession or crisis, which also breaks the income trajectory, and instead proposes fiscal solutions to avoid side effects.